Study of haematological, biochemical profile and clinical presentation in dengue positive patients: 82 cases - Patel, Mubin I.; Patel, Abhishek; Patel, Avani; Patel, Sharmistha; Padsala, Suresh (International Journal of Research in Medical Sciences, 2018)
Background: Dengue Fever (DF) is a self-limiting disease caused by arbovirus and transmitted by Aedes mosquitoes (Aedes aegypti and Aedes albopictus). It is one of the 17 neglected tropical diseases by WHO. Diagnosis of dengue depends mainly on the detection of IgM and IgG antibody, and NS1 antigen. Methods: The study was carried out in Department of Pathology, affiliated with a government hospital. It includes 82 dengue patients, admitted from August 2015 to August 2016. Haematological, biochemical profile, clinical signs and symptoms were recorded. The Tourniquet test was performed in all the patients on admission. Grading of dengue: DF/DHFI/DHFII/DHFIII/DHFIV. Grade III and IV were collectively called as Dengue Shock Syndrome. Results: Total 82 Dengue positive cases were studied, 52 (63%) were males and 30 (37%) were females. 24 (29%) patients were recorded in September 22 (27%) in October 19 (23%) in August. 12 (14.60%) had positive tourniquet test. Thrombocytopenia was present in 86.5 % patients. Majority cases were of classical dengue fever 51 (62.20%), 14 (17.07%) were of DHF I, 12 (14.63%) were of DHF II, 3 (3.66%) were of DHF III and 2 (2.44%) were of DHF IV. Conclusions: It is very important to correlate clinical examination with haematological and biochemical profile in dengue patients. Hematocrit value, leucopenia, thrombocytopenia, raised liver enzymes is very important to monitor dengue cases in their initial stages and thus facilitate early treatment. This would minimize morbidity and mortality arising out of serious complications of dengue fever.